Association between tumour necrosis factor-α inhibitors and risk of serious infections in people with inflammatory bowel disease: nationwide Danish cohort study - Nyboe Andersen, Nynne (BMJ, 2015)
Objective To investigate whether people with inflammatory bowel disease treated with tumour necrosis factor-α (TNF-α) inhibitors are at increased risk of serious infections. Design Nationwide register based propensity score matched cohort study. Setting Denmark, 2002-12. Participants The background cohort eligible for matching comprised 52 392 people with inflammatory bowel disease, aged 15 to 75 years, of whom 4300 were treated with TNF-α inhibitors. To limit confounding, a two stage matching method was applied; firstly matching on age, sex, disease duration, and inflammatory bowel disease subtype, and secondly matching on propensity scores (1:1 ratio); this yielded 1543 people treated with TNF-α inhibitors and 1543 untreated to be included in the analyses. Main outcome measures The main outcome was any serious infection, defined as a diagnosis of infection associated with hospital admission. Cox regression was used to estimate hazard ratios for two risk periods (90 and 365 days after the start of TNF-α inhibitor treatment). Hazard ratios of site specific serious infections were obtained solely for the 365 days risk period. Results Within the 90 days risk period, 51 cases of infection were observed in users of TNF-α inhibitors (incidence rate 14/100 person years), compared with 33 cases in non-users (9/100 person years), yielding a hazard ratio of 1.63 (95% confidence interval 1.01 to 2.63). Within the risk period of 365 days, the hazard ratio was 1.27 (0.92 to 1.75). In analyses of site specific infections, the hazard ratio was above 2 for several of the subgroups but only reached statistical significance for skin and soft tissue infections (2.51, 1.23 to 5.12). Conclusions This nationwide propensity score matched cohort study suggests an increased risk of serious infections associated with use of TNF-α inhibitors within the first 90 days of starting treatment and a subsequent decline in risk. This calls for increased clinical awareness of potential infectious complications among people with inflammatory bowel disease using these drugs, especially early in the course of treatment.